2014
DOI: 10.7314/apjcp.2014.15.14.5873
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of HIF-1α, BNIP3 and PI3KC3: Hypoxia-Induced Autophagy Predicts Cholangiocarcinoma Survival and Metastasis

Abstract: Hypoxia and autophagy are known to facilitate tumor progression. We here aimed to investigate the role of hypoxia-associated autophagy in cholangiocarcinoma (CCA) survival and metastasis. Immunostaining of hypoxicresponsive proteins (HIF-1α and BNIP3) and a key regulator of autophagy (PI3KC3) were examined in CCA tissues and their expression levels were compared with clinicopathological parameters. A hypoxia mimicking condition (CoCl 2 treatment) was also tested regarding CCA cell functions. Our results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…This experimental study points to a fundamental effect of CQ on CCA cell metastasis under hypoxiamimicking condition. We created an in vitro hypoxia-like state by treatment of two CCA cell lines with 100 μM of CoCl 2 (Liu et al, 1999;Law et al, 2012;Thongchot et al, 2014). We demonstrated that CoCl 2 -induced hypoxia significantly increased metastases in both CCA cell lines, using a transwell migration assay.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This experimental study points to a fundamental effect of CQ on CCA cell metastasis under hypoxiamimicking condition. We created an in vitro hypoxia-like state by treatment of two CCA cell lines with 100 μM of CoCl 2 (Liu et al, 1999;Law et al, 2012;Thongchot et al, 2014). We demonstrated that CoCl 2 -induced hypoxia significantly increased metastases in both CCA cell lines, using a transwell migration assay.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have demonstrated that the behavior of CCA cell lines is significantly affected by hypoxia (Seubwai et al, 2012;Thongchot et al, 2014). We applied 100 μM CoCl 2 to provide the hypoxic-mimic conditions for CCA cell culture, and trans-migrating cells were evaluated.…”
Section: Cq Suppressed Cca Cell Migration Under the Cocl 2 -Induced Hmentioning
confidence: 99%
See 1 more Smart Citation
“…A major mechanism linking between inflammation and CCA is related to the generation of free radicals such as superoxide anion (O2¯•), nitric oxide (NO) and other reactive oxygen (ROS) * and nitrogen species (RNS) which cause DNA damage and the alteration of gene expressions in both a hamster animal model and humans (Jaiswal et al, 2000;Pinlaor et al, 2003;Thanan et al, 2008;Yongvanit et al, 2012b). Regarding to the molecular mechanism underlining CCA progression, there are some studies have demonstrated aberrant expression of potential genes involving in CCA (Kunlabut et al, 2012;Namwat et al, 2012;Thongchot et al, 2014). In addition, several studies show that oxidative DNA damage plays a role in not only DNA mutation but also genetic instability and epigenetic changes which could be involved in all steps of inflammation-related carcinogenesis (Murata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical importance of this situation is the fact that the intercellular fluid causes a decrease in the effectiveness of the treatment without being given at the targeted therapeutic dose into the tumor tissue of the applied antitumoral agents, besides the possibility of that fluid movement to facilitate the lymphatic invasion and metastasis. In the meantime, the hypoxic microenvironment caused by the insufficient circulation has a negative influence on the effectiveness of the radiation therapy (Milosevic et al, 2001;Salnikov et al, 2003;Heldin et al, 2004;Thongchot et al, 2014).…”
mentioning
confidence: 99%